Determination of Standard Parameters of Acorn Squash Leaves - Oleh S. Shpychak (Journal of Global Pharma Technology, 2020)
One of the priority tasks of pharmacy is to find new sources of raw materials for the medicinal products. The purpose of this work is to determine a number of indicators of the quality of promising medicinal raw materials that are the leaves of acorn squash Cucurbita pepo (Cucurbitaceae) for the creation of regulatory and technical documentation. For our research one of the most competitive kind -